Measuring and Modelling Whole-Tree Gas Exchange - Lloyd,J; Wong,SC; Styles,JM; Batten,D; Priddle,R; Turnbull,C; Mcconchie,CA (Australian Journal of Plant Physiology, 1995)
Diurnal patterns of CO2 and water vapour exchange were determined for Macadamia integrifolia and Litchi chinensis trees enclosed in whole-tree gas exchange chambers at Alstonville, New South Wales (28.5ºS) during October and November 1991. Whole-tree gas exchange responses to photon irradiance (I), ambient partial pressure of CO2 (Ca) and vapour pressure deficit (D) were similar to those normally observed for individual leaves. Nevertheless, at a given I (above approximately 500 μmol quanta m-2, s-1) stomatal conductances (gs) and CO2 assimilation rates (A) were higher under overcast, as opposed to clear sky conditions. This difference was maintained even when A and gs were examined as a function of sun angle. Combined with a simple light interception model, nested quadratic equations combining stomatal responses and biochemical characteristics of individual leaves were found to provide excellent descriptions of the gas exchange responses of the isolated trees. This indicates a close to optimal partitioning of photosynthetic machinery throughout the canopy. From the whole-tree gas exchange model it was found that higher A and gs under overcast conditions are attributable to both lower T1 and D as well as to a more uniform distribution of irradiance across the canopy surface.